Young Children on the Grow Health, Activity, and Education in the Preschool Setting. Teacher Education Monograph No. 13 / Charlotte M. Hendricks, Ed. - Hendricks, Charlotte M. (ERIC Clearinghouse on Teaching and Teacher Education, 1992)
Preschool programs can and should be designed to incorporate comprehensive health and physical education. This monograph presents information which is useful to adults interested in increasing their knowledge of health, movement, and physical education as these areas relate to young children. The publication is organized into 14 chapters as follows: (1) "Young Children: An Introduction" (C. J. Smith); (2) "Early Childhood Education: The National Scene" (M. Hanson); (3) "Movement and Motor Development in Early Childhood" (D. Hester); (4) "Physical Activity of Young Children in Relation to Physical and Mental Health" (H. Taras); (5) "Dance in Early Childhood Education" (S. Stinson and Others); (6) "Educating Young Children about Health" (D. Macrina); (7) "The Impact of Public Law 99-457 on Health, Physical Education, Recreation, and Dance" (J. Aldridge); (8) "Preschool Children with Developmental Delays/Disabilities: Individual Differences and Integration" (C. Sherrill); (9) "Motoric and Fitness Assessment of Young Children" (C. Branta); (10) "Health Assessment and Intervention Techniques for 3-, 4-, and 5-Year-Old Children" (V. Hertel); (11) "Health Promotion through Parent Involvement in Early Childhood Education" (M. Kostelnik); (12) "Health and Safety Education for Caregivers" (L. Hofer); (13) "Playground Management and Safety" (L. Bowers); and (14) "Injury Prevention in the Child Care Setting" (A. Chang). Lists of figures and tables complete the document, and references are appended to chapters. (LL)